The Dry Fog of 1783: Environmental Impact and Human Reaction to the Lakagígar Eruption - Eyþór Halldórsson 1981- (2013)
In the year 1783, an unusual fog covered the atmosphere over a large part of the Northern Hemisphere, persisting for a period of up to three months. In particular, the summer in Europe was characterized by the appearance of this phenomenon. Many contemporaries described it as a dry fog. The origin of this was the Lakagígar volcanic eruption of 1783-1784 in Iceland. This research focuses on the environmental impact of the eruption in Iceland and Europe, and analyzes how contemporaries reacted to its influence and what meaning they derived from it. The event is known to be one of the largest fissure eruptions in historical times. As a result of the volcanic activity, notorious amounts of volcanic gases were released into the atmosphere which formed the infamous fog. In Iceland, the volcanic pollution damaged crops and vegetation, and had a disastrous consequence for livelihood in the country. In that sense, the eruption was one of the primary causes of the Haze Famine of 1783-1785, where one-fifth of the Icelandic population perished. In Europe, the volcanic fog wielded an influence on communities that were oblivious of its origin. While the unusual atmospheric condition caused terror among common people, the Enlightenment thinkers of the day tried hard to reason out its origin. However, the boundary of scientific knowledge in late-18th century Europe contributed to a confused identification of the event. In that sense, the dry fog of 1783 challenged people’s world-views. Unlike the Icelandic experience, the environmental impact of the fog does not appear to have been significant in Europe. Despite adverse effects on vegetation due to the aerial pollution being identified in the northern and western part of the continent it did not affect the progress of the summer harvest. It is also difficult to determine whether the volcanic pollution had any effects on mortality in Europe. By highlighting these results, this research challenges notions that have been presented in recent years on the environmental influence of ...